Modeling forward-looking state-level farm financial stress using bank loan delinquency data - Warren, Bryston (My University, 2025)
During the past 20 years, and since the restructuring of the USDA Economic Research Service’s farm economy division, minimal work has been done to track farm financial measures at the state or regional levels. Instead, farm financial research has tended to focus on national-level measures. Policymakers often react to stakeholder testimony about concerns of waning farm income when creating ad-hoc agricultural economic relief policies. Having a more robust leading indicator of state-level farm financial well-being can improve policies being implemented and lead to better timing of ad-hoc economic recovery payments. This study aggregates a commonly used banking stress-test measure of loan delinquency rate as a proxy for the counter-party farm financial well-being. Loan delinquency rates in this study were estimated by using Federal Reserve commercial bank and Farm Credit call data to compute a combined delinquency rate for each state to measure farm financial stress. Variables for the models included crop revenues, livestock revenues, lagged government payment revenues, total expenses, and lagged delinquency rates. Historical state-level explanatory variable data is from the Economic Research Service (ERS) and then 10-year forward-looking estimates are from Rural & Farm Finance Policy Analysis Center (RaFF). In comparing three alternative models of individual state models, pooled panel state models, and state delinquency rates with national explanatory variable data, the pooled panel state models provided results that are consistent with economic theory and returned a high statistical fit. The lagged delinquency rates had the largest impact on loan delinquency rates, indicating that hard, or good, times of financial stress will linger in the following years. While direct government payments also showed to be a useful tool in supporting producers financially.
Keywords: Agricultural finance; Farm; Livestock; Credit; Stress